2010
DOI: 10.1200/jco.2009.22.8585
|View full text |Cite
|
Sign up to set email alerts
|

90Y-Edotreotide for Metastatic Carcinoid Refractory to Octreotide

Abstract: (90)Y-edotreotide treatment improved symptoms associated with malignant carcinoid among subjects with no treatment alternatives. Treatment was well-tolerated and had an acceptable expected AE profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(181 citation statements)
references
References 28 publications
3
165
0
13
Order By: Relevance
“…However, analysis of survival data showed that survival in patients with a partial response might be similar to that in patients with stable disease after PRRT (36)(37)(38)(39). With these findings in mind, for the evaluation of a response, one could consider disease control rates (complete response, partial response, and stable disease), which ranged from 62% to 95% in trials including only patients with progressive disease at baseline (38)(39)(40)(41)(42). Figure 2 shows the efficacy of PRRT in a patient with rectal NET with metastases to the liver.…”
Section: Efficacymentioning
confidence: 99%
“…However, analysis of survival data showed that survival in patients with a partial response might be similar to that in patients with stable disease after PRRT (36)(37)(38)(39). With these findings in mind, for the evaluation of a response, one could consider disease control rates (complete response, partial response, and stable disease), which ranged from 62% to 95% in trials including only patients with progressive disease at baseline (38)(39)(40)(41)(42). Figure 2 shows the efficacy of PRRT in a patient with rectal NET with metastases to the liver.…”
Section: Efficacymentioning
confidence: 99%
“…The response rate to PRRT varies significantly depending on the location of the primary tumor. For example, an SST receptorpositive metastasized ileal NET exhibits a response rate which is much lower than SST receptor-positive metastasized pancreatic NET [26,27,29]. Given these observations, the concept of utilizing PRRT in all well to moderately differentiated gastroenteropancreatic NETs requires critical reassessment.…”
Section: Mechanism Of Action Of Radionuclidesmentioning
confidence: 99%
“…[14][15][16][17] In addition, the majority of studies have shown excellent symptomatic response in >70% of patients. Time to progression in reported studies ranged from 13-29 months.…”
Section: Y-dotatate/dotatoc Anti-tumour Effectsmentioning
confidence: 99%